Rancang Bangun dan Pengujian Penghalang Heliks sebagai Pencampur Udara-Biogas pada Motor Otto - Herbert Hasudungan Siahaan; Armansyah H Tambunan; Desrial; Soni Solistia Wirawan (Jurnal Keteknikan Pertanian, 2020)
A helical barrier as air-biogas mixing device was designed and tested for direct use of biogas from digester in otto cycle generator set. Homogeneity of the air-fuel mixture can give better combustion reaction and increase engine power. The design was based on simulation, which shows that a 0.039 m length of helical barrier gave a 5% increase in power compared to non-helical barrier. Likewise, the simulations also showed that the helical barrier reduced specific fuel consumption (SFC) by 8%. Accordingly, the mixer with helical barrier was designed, and fabricated. Its performance test confirms the improvement resulted by using helical barriers as air-biogas mixer in the engine. The experiment showed that the power increased by 5% when using helical barrier, while SFC decreased by 4.5%. It is concluded that the helical barrier can increase the homogeneity of the mixture resulting in better engine performance. Besides, emissions produced from the engine using a helical barrier also decreased.